ANALYSIS OF A DIRECT SELLING NETWORK FOR AGRIFOOD PRODUCTS - Placido Rapisarda (Chiriotti Editori, 2015)
Sicily has become a food and wine area of great interest. However, conflicts within the supply chains have caused the selling process to become long and complex to the disadvantage of farmers, thereby leading to an information asymmetry between producers and consumers. In order to meet the new needs of the agrifood sector, we developed a theoretical model of organized direct selling that goes beyond regional boundaries, which is an alternative model to farmers' markets and that helps to promote the creation of a network among the operators of Sicilian agrifood supply chains. The aims of this study was to verify the potential of the proposed theoretical model based on a SWOT analysis, which was achieved by collecting data from interviews with the producers involved in the Sicilian agrifood supply chains, and with the main stakeholders involved.